Pharmacodynamics of tegoprazan and revaprazan after single and multiple oral doses in healthy subjects - Sunwoo, Jung; Ji, Sang Chun; Oh, Jaeseong; Ban, Mu Seong; Nam, Ji Yeon; Kim, Bongtae; Song, Geun Seog; Yu, Kyung‐Sang; Jang, In‐Jin; Lee, SeungHwan (Alimentary pharmacology & therapeutics, 2020)
Summary Background Potassium‐competitive acid blockers (P‐CABs) are emerging as novel treatments for acid‐related disorders including gastroesophageal reflux disease. Tegoprazan and revaprazan are approved P‐CABs in South Korea, but the pharmacodynamics and safety/tolerability of the two drugs have never been compared. Aims To evaluate the pharmacodynamics and safety/tolerability of tegoprazan and revaprazan after single and multiple oral doses Methods A randomised, open‐label, active‐controlled study was conducted in Helicobacter pylori‐negative healthy Korean male subjects. Tegoprazan 50 mg or revaprazan 200 mg was administered orally, once daily for 7 days; 24‐h intragastric pH monitoring and serum gastrin were measured for pharmacodynamic evaluation. Safety parameters including serum microRNA‐122 (miR‐122) level were also collected. Results After a single dose, the %Time pH ≥4 for tegoprazan was greater than that for revaprazan (54.5% vs 25.1%). After multiple doses, the %Time pH ≥4 for tegoprazan was also greater than that for revaprazan (68.2% vs 25.3%). %Time pH ≥4 during 12 hours at nighttime for tegoprazan was greater than that for revaprazan (71.8% vs 31.9%). The changes in the serum gastrin were not clinically significant for either drug. Despite the slight increases of serum miR‐122 for each drug, tegoprazan and revaprazan were well tolerated considering other safety parameters including AST and ALT levels. Conclusion Tegoprazan 50 mg showed stronger gastric acid suppression than revaorazan 200 mg. Both drugs were well tolerated.